Peranan Filantropi Islam Dalam Pemulihan Ekonomi Umat Akibat Pandemi Covid-19: Studi Kasus pada BAZNAS Kab. Maros - Akbar Akbar; Nurfiah Nurfiah; Trisno Wardy Putra (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Due to the massive spread of the Corona virus outbreak which later changed its status to a pandemic, every country has to clean up and implement mitigating regulations. The form of policy implemented in order to reduce the spread of the Covid-19 virus is by social or physical distancing. However, this restrictive movement does not always run effectively on state conditions. The implementation of this policy will at least have a negative effect on activities in the economy. This situation causes shocks to the economy both at the global and national levels. The type of research used by the author is qualitative research. The researcher directly observed events in the field that were directly related to the role of Islamic philanthropy in the economic recovery of the Ummah in Maros Regency. Qualitative data through semi-structured interviews were collected from 2 main subjects, namely the amil or BAZNAS Maros Regency and Mustahik or the beneficiaries. In addition, this study uses observational and documentary techniques. While the data analysis and validation techniques used data reduction, data presentation, and drawing conclusions. The results show that Islamic philanthropy has an important role in restoring the economy and prospering the underprivileged people affected by the pandemic. Beneficiaries of Islamic philanthropic funds feel a big role in daily economic recovery, including through the program Village Baznas Microfinance (BMD). Keywords : Covid-19 Pandemic, Islamic Philanthropy, and Economic Recovery